español - Estupiñán, Katrin Yohanna
The purpose of this article is to invite thought to the current situation of appropriation, valuation and knowledge of cultural heritage by the communities around the legacy of the “Ruta Libertadora” led by Simón Bolívar in 1819. Likewise, it delved into an analysis of the results obtained from the historical assessment research regarding the stages of the liberator’s passage in the provinces of Tundama and La Libertad. It also links the need of proposing certain strategies articulated to the National Government to promote spaces for recovery and revaluation of the Cultural Heritage product of the Liberating Campaign.